DEVELOPMENT OF PARENTING MODULE FOR STUDENTS' PARENT IN JUNIOR HIGH SCHOOL: A NEEDS ANALYSIS AND FEASIBILITY STUDY - Deni Hermawan, Asep; Mansur Tamam, Abas; Rosyadi, A. Rahmat; Abdul Nasir Zakaria, Gamal; Kawakip, Akhmad Nurul (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2025)
The increasing trust of the Indonesian people in Islamic boarding schools as educational institutions is evidenced by the increasing number of students from 677 thousand in 1977 to 4.4 million in 2020. Unfortunately, the level of involvement of guardians/parents in their children's education is still minimal, resulting in less than optimal educational outcomes. Guardians/parents have also not aligned the education model at home with the vision of the Islamic boarding school when their children return home. The parenting modules available online are considered unsuitable for the ‘walisantri’ guidelines. Therefore, it is necessary to develop a parenting module that is suitable for them. This study was conducted to meet these needs. Based on a questionnaire distributed to Islamic boarding school administrators and ‘walisantri’ domiciled in West Java, it was found that there was a need for a parenting module for ‘walisantri’. The parenting module developed through R&D is specifically for junior high school students. This research and development use the ADDIE model with data collection techniques in the form of questionnaires distributed to Islamic boarding school administrators and ‘walisantri’ to ensure their needs for the module, as well as questionnaires for experts to assess the feasibility of the developed module. This study concludes that there is no parenting module in Islamic boarding schools and its existence is greatly needed by Islamic boarding school administrators throughout West Java and ‘walisantri’. Meanwhile, the developed module is very feasible according to experts to be used as a guideline by Islamic boarding school administrators and ‘walisantri’.